2017
DOI: 10.1016/j.biortech.2017.06.123
|View full text |Cite
|
Sign up to set email alerts
|

Ferric chloride assisted plasma pretreatment of lignocellulose

Abstract: In this study, a novel pretreatment for spent coffee waste (SCW) has been proposed which combines two techniques viz. atmospheric air plasma and FeCl to create a superior pretreatment that involves Fenton chemistry. The pretreatment was optimised employing Taguchi Design of Experiments, and five parameters were taken into consideration viz. biomass loading, FeCl concentration, HSO concentration, plasma discharge voltage and treatment time. The composition analysis of the pretreated SCW revealed substantial amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…This result suggested that the hemicellulose degradation was faster than delignification during NaOH or AHP pretreatment, which did not decrease the lignin content in pretreated substrates. The peak at 898 cm −1 attributed to the β-glycosidic linkages in cellulose, became intensive after pretreatment, which was in agreement with the increment of glucan after pretreatment, as confirmed in Table 1 [28]. Taken together, the FT-IR analysis was in accordance with the chemical analysis data, retained the major cellulose in pretreated substrates by selective breaking functional groups and chemical bonds, and presented an enhanced exposure of cellulose for enzyme accessibility because of the degradation of hemicellulose and lignin [7].…”
Section: Resultssupporting
confidence: 76%
“…This result suggested that the hemicellulose degradation was faster than delignification during NaOH or AHP pretreatment, which did not decrease the lignin content in pretreated substrates. The peak at 898 cm −1 attributed to the β-glycosidic linkages in cellulose, became intensive after pretreatment, which was in agreement with the increment of glucan after pretreatment, as confirmed in Table 1 [28]. Taken together, the FT-IR analysis was in accordance with the chemical analysis data, retained the major cellulose in pretreated substrates by selective breaking functional groups and chemical bonds, and presented an enhanced exposure of cellulose for enzyme accessibility because of the degradation of hemicellulose and lignin [7].…”
Section: Resultssupporting
confidence: 76%
“…The solubility of PMP in ethanol, water, acetone, methyl alcohol, chloroform, and diethyl ether was assessed in accordance with the British pharmacopoeia specification (Kannan, Manivannan, Balasubramaniam, & Kumar, ). The nature of PMP was demonstrated by Ferric chloride test (Ravindran, Sarangapani, Jaiswal, Cullen, & Jaiswal, ), Iodine test and Felhing’s test (Xu et al, ). The protein, uronic acid, and total sugar content in PMP were, respectively, assayed by Coomassie brilliant blue method, sulphuric acid‐carbazole spectrophotometric method, and phenol‐sulfuric acid method (Kong et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, obtaining fatty acid ethyl esters rather than fatty acid methyl esters increased the overall renewability [69]. Another approach to valorize the SCG introduced a combination atmospheric air plasma and FeCl 3, in order to create a superior pretreatment that involve Fenton chemistry for a more effective delignification prior to enzymatic treatment and bioethanol production by S. cerevisiae [70]. Using S. cerevisiae, bioethanol was also obtained from other wastes such as coffee juice and mucilage.…”
Section: Spent Coffee Grounds and Biofuelsmentioning
confidence: 99%